PROSES KULTIVASI Spirulina platensis MENGGUNAKAN POME (Palm Oil Mill Effluent) SEBAGAI MEDIA KULTUR DALAM RECEWAY OPEN POND BIOREACTOR - Erlinda Khoirunisa; Elisa Mutiah; A Abdullah (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
Spirulina platensis is being cultivated in POME as a medium using raceway open pond bioreactor during 5 days. Purpose of this research, which has POME concentration (3×, 4×, 5× diluted) and feed loading concentration of Spirulina platensis (0.443 g/L; 0.618 g/L; 0.952 g/L) as variables, are learning the effect of those variables to the Spirulina platensis growth and finding the best variable composition for Spirulina platensis growth. The response for this research is dry weight of Spirulina platensis.The result shows that POME which is five times diluted as a medium gives the highest dry weight of Spirulina platensis, it is 0.7592 g/L. For the feed loading concentration of Spirulina platensis, the best result shown at 0.443 g/L feed loading concentration which gives 0.9932 g/L dry weight of Spirulina platensis. It can be conclude that POME which is five times diluted and 0.443 g/L feed loading concentration of Spirulina platensis give the best result for Spirulina platensis growth. From this research, it is expected to have a  further research in a longer cultivation period of Spirulina platensis so that it can be a contribution for Spirulina platensis cultivation which can be commercially exploited for the supplements in human food, animal feed, beauty products and pharmaceuticals